The role of augmented reality in supporting deep learning within the merdeka curriculum: A systematic literature review in chemistry education - Agussalim, Hastuti (Universitas Papua, Manokwari, Indonesia, 2025)
Chemistry education frequently faces challenges due to the abstract nature of chemical concepts, limited visual media, and insufficient student engagement. In contrast, the Merdeka Curriculum highlights the importance of deep learning, emphasizing conceptual understanding, scientific reasoning, and meaningful learning experiences. Augmented Reality (AR) offers promising affordances for addressing these issues through interactive, context-rich three-dimensional representations. This study employed a PRISMA-based Systematic Literature Review (SLR) of 12 empirical articles published between 2015 and 2025 in Scopus-indexed databases, major international publishers, and accredited SINTA journals. The findings reveal a marked increase in AR research in chemistry education between 2023 and 2025, with research and development (R&D) and quasi-experimental designs predominantly conducted at the senior secondary level. Across studies, AR consistently enhances conceptual understanding, multi-level representational competence, higher-order thinking skills, and student engagement. Moreover, AR aligns strongly with the pedagogical principles of the Merdeka Curriculum, particularly project-based learning, authentic assessment, differentiated instruction, and the development of the Pancasila Student Profile. These insights position AR as a strategic innovation for advancing deep and meaningful chemistry learning. Further research is recommended to investigate the long-term effects of AR and its integration within inquiry-based and project-based instructional models.